English English - Fitri Windayani; Kartika Ratna Pertiwi (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the feasibility of LKPD based on scientific inquiry to improve students' critical thinking skills and collaboration skills. The type of research used is research and development with research procedures using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research is limited to the feasibility test of LKPD based on scientific inquiry at the development stage. The assessment of the results of the validity test and the practicality test of the questionnaire is interpreted on a Likert scale. Based on the data analysis, the following results were obtained: the validity test of teaching materials in the form of LKPD based on scientific inquiry obtained an average validity of the eligibility media for teaching materials of 92.75% and 85% for material eligibility. The practicality test conducted by Biology educators obtained an average score of 75% and 79% for students